PROBLEMS OF ECOLOGICAL HUMAN RIGHTS PROTECTION IN UKRAINE - Толкачова, Ірина Анатоліївна; Кириченко, Вікторія Вячеславівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to research human rights protection problems in Ukraine in connection with environmental pollution and provide proposals of their solution. Research methods: in this article general scientific and special methods were used. With the help of the dialectical method of cognition, the subject matter of research was considered in unity of its social content and legal form, peculiarities of elements of the exercise of right to a secure environment, revelation of interactions between them were also taken into account. The legal and historical method was used to analyze the evolution of protection of ecological human rights in Ukraine. When writing the article, the following philosophical methods of research were also used: analysis, synthesis, abstraction, deduction and others. An integrated approach to the use of the aforementioned scientific methods made it possible to comprehensively explore problems of ecological human rights protection. Results: the state of the environment in Ukraine continues to deteriorate. Conservation and rational use of natural resources, in particular, stability of the global climate system is one of the most important and urgent problems of our time. The main unresolved and global problem of Ukraine, which concerns all spheres of its activities, including environmental policy of the state, is irresponsibility and inaction of the authorities, non-understanding of the value of nature and natural resources. Gradual solution of a large number of cases on violation of ecological rights of citizens is possible only if some changes to ecological legislation are made, as well as inclusion to this work of the bodies of local self-government, civil organizations and public condemnation of all those structures, managers of companies and organizations, which destroy the ecology and consequently possibilities to exist in a harmonious and clean environment. Discussion: state of protection of ecological human rights in Ukraine.